Menjelajahi Gaya Kepemimpinan dan Pengaruhnya terhadap Perilaku Kerja Inovasi Karyawan: Tinjauan Literatur Sistematis - Handiman, Unang Toto; Adam, Duki; Amalia, Dinda; Purba, Daniel Wisuda; Sari, Sherly Puspita; Suhendi, Dede (ICON Publisher, 2025)
This study aims to give a thorough synthesis of the state of the art in the subject by methodically reviewing the literature to identify important leadership philosophies that impact employee creativity. The PRISMA procedure was adopted to carry out a systematic literature review (SLR). In order to find relevant peer-reviewed papers released between 1995 and 2023, the study performed a systematic search of scholarly databases, including Sciencedirect, Emerald, and MDI. Recognition, screening, qualification assessments, and inclusion phases were all part of the selection process. To find recurrent patterns and connections, the data taken from the chosen studies was subjected to theme synthesis and coding analysis. The findings reveal that transformational and participative leadership styles are the most influential in fostering employee IWB. Key factors contributing to this relationship include leader support, motivation, and an organizational culture that encourages risk-taking and knowledge sharing. Additionally, transactional leadership was found to have a mixed impact depending on organizational context and employee autonomy levels. The study reveals that employee IWB is greatly influenced by leadership styles, with transformational leadership having the most beneficial benefits. By providing perspectives into organizational policies and leadership development initiatives targeted at generating innovation, the research advances both theory and practice. The moderating effect of industry-specific factors and organizational culture should be investigated in future studies. By using a methodical and rigorous approach, this study fills gaps in the literature and lays the groundwork for future empirical research by offering a thorough synthesis of leadership styles in relation to IWB into the relationship between innovation and leadership styles.